Desain Evaporator Dan Pengujian Kondisi Operasi Optimal Pada Desain Peralatan - Achmad Faisal Faputri (Politeknik Akamigas Palembang, 2016)
Evaporator tool serves to separate water from ethanol content, using the heater in the form of water vapor or steam has a high temperature, so that can heat the ethanol inside the shell on a Evaporator tool. In designing tool Evaporator many important things that need to be noticed, ranging from understanding the workings and functions of the tool Evaporator, designing, material selection until the evaporator equipment design process, it aims to get the maximum results from the tools work Evaporator. The effect of temperature is an important aspect in the process that occurs within the tool Evaporator that will determine the effectiveness of the evaporator so as to separate the water content in ethanol. The optimum conditions of the circuit Evaporator equipment that it’s designed on temperature of 230 oF inlet tube and outlet tube 226.4 oF and 89.6 oF shell inlet and outlet shell 176 oF.